How Sexually Dimorphic Are Human Mate Preferences?. (August 2015) - Conroy-Beam, Daniel; Buss, David M.; Pham, Michael N.; Shackelford, Todd K.
Previous studies on sex-differentiated mate preferences have focused on univariate analyses. However, because mate selection is inherently multidimensional, a multivariate analysis more appropriately measures sex differences in mate preferences. We used the Mahalanobis distance ( D ) and logistic regression to investigate sex differences in mate preferences with data secured from participants residing in 37 cultures ( n = 10, 153). Sex differences are large in multivariate terms, yielding an overall D = 2.41, corresponding to overlap between the sexes of just 22.8%. Moreover, knowledge of mate preferences alone affords correct classification of sex with 92.2% accuracy. Finally, pattern-wise sex differences are negatively correlated with gender equality across cultures but are nonetheless cross-culturally robust. Discussion focuses on implications in evaluating the importance and magnitude of sex differences in mate preferences.